The COVID-19 Pandemic and it effect on human capital and financial performance: Evidence from Serbian banks - Goran Pavlović (Anali Ekonomskog fakulteta u Subotici, 2024)
Human capital holds significant importance for banks as it includes specific knowledge and skills. It serves as a crucial determinant of financial performance. However, human capital is susceptible to various factors that can exert negative effects. The COVID-19 stands as one such factor, necessitating the restructuring of banks and potentially resulting in a depreciation of human capital value and subsequent performance decline. The objective of the research is to investigate the influence of the COVID-19 pandemic on the human capital of banks in the Republic of Serbia and evaluate its implications on financial performance. The research spanned across all banks operating in the Republic of Serbia throughout the period of 2019 to 2021. The Wilcoxon Signed Rank test was employed to assess the difference in human capital value over the observed period. Furthermore, the regression analysis was implemented to investigate the impact of human capital on ROA, ROE, and NPM. Results showed that COVID-19 pandemic has led to a decrease in the value of human capital in banks in the Republic of Serbia. The financial performance of banks is positively influenced by human capital in the short term. However, over the long term, the value of human capital depreciates, resulting in a diminishing impact on financial performance.